Promotion of oral health in schoolchildren in the framework of a comprehensive collective intervention, conducted in the period 2013-2015, in Córdoba, Argentina - Cornejo, Lila Susana (2022)
Fil: Cornejo, Lila Susana. Universidad Nacional de Córdoba. Facultad de Odontología; Argentina.